2022
DOI: 10.1021/acsmedchemlett.2c00111
|View full text |Cite
|
Sign up to set email alerts
|

1,3-Dioxane-Linked Novel Bacterial Topoisomerase Inhibitors: Expanding Structural Diversity and the Antibacterial Spectrum

Abstract: Antibacterial resistance continues its devastation of available therapies. Novel bacterial topoisomerase inhibitors (NBTIs) offer one solution to this critical issue. Two series of amine NBTIs bearing tricyclic DNA-binding moieties as well as amide NBTIs with a bicyclic DNA-binding moiety were synthesized and evaluated against methicillin-resistant Staphylococcus aureus (MRSA). Additionally, these compounds and a series of bicyclic amine analogues displayed high activity against susceptible and drug-resistant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…Although interactions between other novel bacterial topoisomerase inhibitors and WT gyrase and topoisomerase IV have been reported, the mechanisms underlying resistance to these compounds and to gepotidacin have yet to be explored. The studies presented here show that simultaneous mutations in both GyrA P35 and ParC D79 are required for a decreased susceptibility to gepotidacin in E.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although interactions between other novel bacterial topoisomerase inhibitors and WT gyrase and topoisomerase IV have been reported, the mechanisms underlying resistance to these compounds and to gepotidacin have yet to be explored. The studies presented here show that simultaneous mutations in both GyrA P35 and ParC D79 are required for a decreased susceptibility to gepotidacin in E.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study that characterized the effects of gepotidacin on S. aureus gyrase found that the compound shares many mechanistic features with earlier preclinical candidate novel bacterial topoisomerase inhibitors. ,, However, virtually nothing is known regarding the actions of gepotidacin on topoisomerase IV. , Because of the clinical promise of gepotidacin against urinary tract infections, it is important to characterize how this compound affects the activities of both gyrase and topoisomerase IV in E. coli.…”
mentioning
confidence: 99%
See 1 more Smart Citation